2015
DOI: 10.1109/access.2015.2437903
|View full text |Cite
|
Sign up to set email alerts
|

Runtime Precoding: Enabling Multipoint Transmission in LTE-Advanced System-Level Simulations

Abstract: System-level simulations have become an indispensable tool for predicting the behavior of wireless cellular systems. As exact link-level modeling is unfeasible due to its huge complexity, mathematical abstraction is required to obtain equivalent results by less complexity. A particular problem in such approaches is the modeling of multiple coherent transmissions. Those arise in multiple-input-multipleoutput transmissions at every base station but nowadays so-called coordinated multipoint (CoMP) techniques have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…9a, it is observed that the results scale approximately linear with the number K of UEs and with the simulation length N TTI . Such behavior was already observed in [22] together with a more detailed description of its origins. In this paper, our main interest is on the impact of the elevation direction and the application of the 3GPP 3D channel model for interfering channels on the simulation run time.…”
Section: Simulation Run Timesmentioning
confidence: 83%
See 3 more Smart Citations
“…9a, it is observed that the results scale approximately linear with the number K of UEs and with the simulation length N TTI . Such behavior was already observed in [22] together with a more detailed description of its origins. In this paper, our main interest is on the impact of the elevation direction and the application of the 3GPP 3D channel model for interfering channels on the simulation run time.…”
Section: Simulation Run Timesmentioning
confidence: 83%
“…We now extend this approach by also taking into account the interfering links. We integrate our code into the Vienna LTEA Downlink System Level Simulator (current version v1.8r1375) [22]. The simulator is implemented in object-oriented MAT-LAB and is made openly available for download under an academic, non-commercial use license.…”
Section: Simulation Run Times and Throughput Performance Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…An algorithm was developed in Reference [8] in order to optimise the number of RRUs deployed in a network using game theory. Multipoint transmission coordination of distributed RRUs has been investigated in References [9,10]. While the first investigation on using remote antennas in the mmWave band was introduced in Reference [11], where the author has demonstrated the importance of remote antennas on minimising the shadow fading of wireless networks in the Local Multipoint Distribution Service (LMDS) band.…”
Section: Introductionmentioning
confidence: 99%